THE INFLUENCE OF THE FERTILIZER SYSTEM ON THE PRODUCTIVITY OF CORN - Марініч, Любов; Ласло, Оксана; Цуревський, Віталій (SWorldJournal, 2024)
Topicality. You can get a high yield of corn in all areas of Ukraine, but first of all you need to choose the right soil cultivation system, correctly calculate and carry out the fertilization system. Problem definition. In order to obtain a high yield of